Su Friedrich - Mennel, Barbara Caroline (Contemporary film directors., 2023)
"With acclaimed films like Sink or Swim and The Odds of Recovery, Su Friedrich's body of work stands at the forefront of avant-garde and Queer cinema. Barbara Mennel examines the career of an experimental auteur whose merger of technical innovation and political critique connects with both cinephiles and activists. Friedrich's integration of cinematic experimentation with lesbian advocacy serves as a beginning rather than an end point of analysis. With that in mind, Mennel provides an essential overview of the filmmaker's oeuvre while highlighting the defining characteristics of her artistic and political signature. She also situates Friedrich within the cultural, political, and historical contexts that both shape the films and are shaped by them. Finally, Mennel expands our notion of auteurism to include directors who engage in collaborative and creative processes rooted in communities"--